DIRECTIONS OF ONOMASTIC RESEARCH INLINGUISTICS - Yakupova Kamila Turmakhammetovna (Western European Studies, 2025)
This article analyzes the directions of onomastic research in linguistics of proper names and common nouns. The historical evidence of culture and language shows that since ancient times, scholars have analyzed works of oral creativity and tried to understand the meaning of various poetic styles and devices, including proper nouns, that is, units associated with names
Keywords: common nouns; Proper names; onomastics